Caesarean Section Under Combined Spinal Epidural Anaesthesia of Pregnant Woman with Takayasu’s Arteritis: Case Report (Annals of Medical Research, 2021)
None
Keywords: Takayasu’s Arteritis; Combined Spinal Epidural Anaesthesia; Caesarean Section.